Estrutura dinâmica e termodinâmica da zona de convergência do Atlântico Sul e sua relação com a oscilação Madden e Jullian - Araujo, Sara Raquel Vaz de (2017)
In the southern summer period over South America, an important system is one of the main modulators of the rainfall regime of the working regions, the SACZ. This system is a nebulosity zone that extends from the Amazon region and it comprehends the midwest and southeast regions, extending it to the southwest of the South Atlantic Ocean. This system will lead to large volumes of rainfall, which can sometimes bring disorders to society, such as landslides, floods, etc. In addition, from the point of view of the predictability of this phenomenon, it has been created an interest in understanding how to adequately represent it in numerical models. One of the most important reasons for this is that in the current context, the global models still can not satisfactorily represent this zone of convergence. Therefore, the purpose of this study was to analyse how the regional model RegCM4 will represent the different atmospheric characteristics when SACZ occurs, due to the importance of the convergence zone thanks to its effects on the regions where the band is stationed. For this, 10 events of SACZ were selected, according to the active phases of the Madden and Jullian Oscillation, being this oscillation important for the tropical convection and in the occurrence of SACZ. After this selection, the average fields of the events of each variable were evaluated, which were: precipitation, surface wind in 850 and 250 hPa, geopotential height in 250 hPa, omega, air temperature, equivalent potential temperature, vorticity, divergence and specific humidity. Finally, the simulations of the RegCM4 model were generally satisfactory for most of the variables, with some displacements regarding the position of some systems that contribute to the formation and maintenance of the SACZ.